2015
DOI: 10.1002/chin.201513052
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Polymer Enzyme Conjugates as Chiral Ligands for Sharpless Dihydroxylation of Alkenes in Organic Solvents.

Abstract: Polymer Enzyme Conjugates as Chiral Ligands for Sharpless Dihydroxylation of Alkenes in Organic Solvents. -(KONIECZNY, S.; LEURS, M.; TILLER*, J. C.; ChemBioChem 16 (2015) 1, 83-90, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Goal of the present study was to explore the potential of poly(2-ethyloxazoline) (PEtOx) as matrix material for the activation of enzymes in electrospun nanofibers in organic solvents. We choose this polymer, because it was found enzyme friendly in solution, in amphiphilic polymer conetworks based on PEtOx, and even as enzyme-polymer conjugates to make the proteins organosoluble (Konieczny et al, 2012), reactive (Konieczny et al, 2014), and even applicable as ligands for organo-metal catalysis (Konieczny et al, 2015;Leurs et al, 2016). Al-Shehri et al (2003) have reported that enzymes can be electrospun from an aqueous solution of commercial PEtOx (M w ¼ 500,000 g/mol).…”
Section: Resultsmentioning
confidence: 99%
“…Goal of the present study was to explore the potential of poly(2-ethyloxazoline) (PEtOx) as matrix material for the activation of enzymes in electrospun nanofibers in organic solvents. We choose this polymer, because it was found enzyme friendly in solution, in amphiphilic polymer conetworks based on PEtOx, and even as enzyme-polymer conjugates to make the proteins organosoluble (Konieczny et al, 2012), reactive (Konieczny et al, 2014), and even applicable as ligands for organo-metal catalysis (Konieczny et al, 2015;Leurs et al, 2016). Al-Shehri et al (2003) have reported that enzymes can be electrospun from an aqueous solution of commercial PEtOx (M w ¼ 500,000 g/mol).…”
Section: Resultsmentioning
confidence: 99%